Influence of H. pylori CagA Coupled with Alcohol Consumption on Cytokine Profiles in Men. Issue 5 (February 2016) - Qu, Baoge; Han, Xinghai; Ren, Guangying; Jia, Yiguo; Liu, Yuanxun; Su, Jiliang; Wang, Zhongdong; Wang, Yafei; Wang, Hui; Pan, Jindun; Liu, Li-li; Hu, Wen-Juan
Abstract : Abstract: The aim of this study was to evaluate the effect of Helicobacter pylori ( H pylori ) cytotoxin-associated gene A (CagA) coupled with chronic alcohol ingestion on cytokine profiles. A total of 215 male subjects were divided into the following 4 groups: 130 alcohol H pylori CagA-negative consumers (CagA−) (group A), 50 alcohol H pylori CagA-positive consumers (CagA+) (group B), 24 nonalcohol H pylori CagA-negative consumers (group C), and 11 nonalcohol H pylori CagA-positive consumers (group D). The serum CagA, C-reactive protein (CRP), interleukin (IL)-6, IL-10, E-selectin, adiponectin (ADP), and tumor necrosis factor-α (TNF-α) levels were measured through enzyme-linked immunosorbent assays (ELISAs). After adjusting for age and mean alcohol drinking history, a multivariable linear regression analysis revealed that the mean daily alcohol consumption, IL-6, TNF-α, and ADP levels were significantly increased with increases in the serum CagA concentrations ( P = 0.008, P = 0.000, P = 0.000, and P = 0.006, respectively). The serum IL-6 and IL-10 levels of group A were significantly lower than those of group B (all P = 0.000). Furthermore, the serum IL-6 and IL-10 levels of groups A and C were significantly lower than those of group D (all P = 0.000), and the serum IL-6 and IL-10 levels of group C were significantly lower than those of group B (all P = 0.000). The serum ADP and E-selectin levels of groups B and D were significantly higher than those of group A ( P = 0.000). The serum ADP levels of group B were significantly higher than those of group C ( P = 0.000), and the serum ADP and E-selectin levels of group C were significantly lower than those of group D ( P = 0.000 and P = 0.005, respectively). Finally, the serum TNF-α levels of groups B, C, and D were significantly higher than those of group A (all P = 0.000), and the serum TNF-α levels of group C were significantly higher than those of group D ( P = 0.005). In conclusion, H pylori CagA may result in significantly higher levels of several inflammatory markers in both alcohol consumers and nonalcohol consumers. However, chronic alcohol ingestion coupled with H pylori CagA positivity does not result in significant changes in cytokine profiles.